Epidemiology of hepatitis C virus infection - Martins, Tatiana (2011)
Epidemiology of hepatitis C virus infectionHepatitis C is a major cause of chronic liver disease worldwide. There is a significant variation in the prevalence of hepatitis C virus (HCV) infection according to the geographic region studied. These discrepancies reflect not only distinct epidemiological characteristics among the populations, but also differences in the methodologies used for the estimates. Despite scarce data, estimates indicate that Brazil is a country with an intermediate prevalence of HCV infection, ranging from 1% to 2%. the most important risk factors for HCV acquisition include injection drug use, blood product transfusion, organ transplantation, hemodialysis, occupational injury, sexual transmission and vertical transmission. Because there is no vaccine and no post-exposure prophylaxis for HCV, the focus of primary prevention efforts should be identification and removal of the risk factors. in this article we review literature regarding the prevalence of HCV infection, particularly in Brazil. in addition, we discuss the pattern of HCV infection according to the age groups and risk factors for HCV acquisition.